Italy’s African foreign policy: between populism and pragmatism - Glubokaya, O.A. (Научно-аналитический вестник Института Европы РАН)
The article considers the peculiarities of Italian-African relations at the present stage and analyses the results of the January Italy-Africa summit. The study presents the main factors that influenced Italy’s interest in moving Italian-African relations to a new level of cooperation, such as the deficit of energy resources, the problem of illegal migration and the desire to take a central place in regional processes. The author examines some of the postulates of Italian foreign policy, including the priority of becoming the centre of African energy with its further distribution to European countries. Since this goal is to be achieved through the implementation of the Mattei Plan, a set of initiatives for the development of Africa, the author pays considerable attention to the conceptual agenda. The summit showed the unilateral focus and modest financial base of the emerging Italian strategy.